Comparison of the Concentration of Local Microorganisms (MOL) in Stale Rice During the Composting Process - Ali, Haidina; Gustiana , Mely; Suyanto, Jipri; Susanty, Sri (YCAB Publisher, 2024)
Background: The symbiotic relationship between microorganisms, specifically decomposing bacteria, and organic material, such as organic waste, leads to the decomposition of the substance and its transformation into compost. Objective: The aim of this study is to assess the efficacy of local microorganisms (MOL) tape in accelerating the decomposition process of organic waste compost. Methods: This research used an experimental study strategy known as